2016
DOI: 10.1111/jbi.12908
|View full text |Cite
|
Sign up to set email alerts
|

Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpetNacella(Mollusca: Patellogastropoda) across the Southern Ocean

Abstract: Aim We use an integrative biogeographical approach to further understand the evolution of an important Southern Ocean marine benthic element, the limpet genus Nacella (Mollusca: Patellogastropoda). Location Southern Ocean.Methods We used multi-locus time-calibrated phylogeny of Nacella at the scale of the whole Southern Ocean to elucidate the underlying processes involved in the origin and diversification of the genus.Results Divergence-time estimates suggest that soon after its origin during the mid-Miocene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 94 publications
4
50
1
5
Order By: Relevance
“…We provide a clear picture of (1) the evolutionary relationships among the sub‐Antarctic Siphonaria species and (2) the geographical distribution of each taxon, to depict biogeographical patterns of the genus at high latitudes. As a consequence of direct development in these higher latitude pulmonates, the main biogeographical patterns in Siphonaria across the Indo‐West Pacific (Dayrat et al., ), and patterns recorded in Southern Ocean near‐shore marine molluscs including Nacella (Gonzalez‐Wevar et al., ) and Doris (Wilson et al., ), we expected to find closely related cryptic species, endemic to each island group. Alternatively, long‐distance dispersal mediated by rafting could play a key role in the biogeography of direct developers like Siphonaria permitting a broad distribution of its representatives across the sub‐Antarctic.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…We provide a clear picture of (1) the evolutionary relationships among the sub‐Antarctic Siphonaria species and (2) the geographical distribution of each taxon, to depict biogeographical patterns of the genus at high latitudes. As a consequence of direct development in these higher latitude pulmonates, the main biogeographical patterns in Siphonaria across the Indo‐West Pacific (Dayrat et al., ), and patterns recorded in Southern Ocean near‐shore marine molluscs including Nacella (Gonzalez‐Wevar et al., ) and Doris (Wilson et al., ), we expected to find closely related cryptic species, endemic to each island group. Alternatively, long‐distance dispersal mediated by rafting could play a key role in the biogeography of direct developers like Siphonaria permitting a broad distribution of its representatives across the sub‐Antarctic.…”
Section: Introductionmentioning
confidence: 97%
“…Biogeographical mechanisms explaining the distribution of southern temperate taxa have been debated for more than a century (Crame, ; Darwin, ; Dell, ; Knox, ; Strugnell, Rogers, Prodöhl, Collins, & Allcock, ). Recently, the literature has been characterized by disagreement over the relative importance of vicariance versus dispersal in the biogeography of the Southern Ocean biota but consensus has emerged about the combined significance of these processes (Clarke, Barnes, & Hodgson, ; Fraser, Nikula, Spencer, & Waters, ; González‐Wevar, Nakano, Cañete, & Poulin, ; Gonzalez‐Wevar et al., ; Moon, Chown, & Fraser, ; Nikula, Fraser, Spencer, & Waters, ; Nikula, Spencer, & Waters, ; Poulin, Gonzalez‐Wevar, Díaz, Gérard, & Hüne, ; Saucède, Pierrat, Danis, & David, ; Waters, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example Matschiner et al (2009) concluded that the lack of genetic structuring between populations of the notothenioid, Gobionotothen gibberifrons, throughout the Scotia Sea could be assigned to the passive transport of their larvae during the pelagic development phase by the ACC as indicated by surface drifter trajectories. The geographic distribution of marine taxa within the Southern Ocean reflects the species life-history traits (including bathymetric ranges, developmental modes and larval lifespans) and the influence of circum-Antarctic current systems (Young et al, 2015;González-Wevar et al, 2017;Moreau et al, 2017).…”
Section: Widespread Antarctic Speciesmentioning
confidence: 99%
“…For this, we used a specific mutation rate (0.85%– 1.15%) previously estimated for nacellid limpets [28]. An age prior with a normal distribution was applied to the most recent common ancestor (tmrca) of Nacellidae (mean, 38; SD, 3.8), an Upper Eocene fossil of Cellana ampla [29].…”
Section: Methodsmentioning
confidence: 99%